A MODERN TEACHER OF RUSSIAN LANGUAGE AND LITERATURE AND HIS CONCEPT OF TEACHING IN FULL AND DISTANCE CONDITIONS (Web of Teachers: Inderscience Research, 2024)
The article discusses the image of a modern teacher in the context of school and university education, as well as in the conditions of full-time and distance Russian education. The article considers the main techniques used by specific teachers in the process of mastering students ' knowledge, skills and abilities in literature. The purpose was to analyze in detail the methods and methods of introducing Russian literature lessons, as well as to consider the main approaches to teaching this discipline. The article also concludes what principles are used by school and university teachers, and whether there are still differences in the conduct of the lesson between a school teacher and a university teacher.